DETERMINANTS OF PROFITABILITY IN CONVENTIONAL BANKS: A REVIEW OF FINANCIAL FACTORS - Mubarok, Faizul; Sauqi, Irfan; Zahra, Ikrimatuz; Putra, Muhammad Zaki Adzkiya (Accounting Department, Politeknik Negeri Bandung, 2024)
This research aims to conduct an in-depth analysis of various factors that influence the profitability of conventional banking. The study focuses on five key financial indicators, namely loan-to-deposit ratio (LDR), Operational Expenses to Operating Income (BOPO), Net Loan performance (NPL), Current Ratio (CR), and Net Interest Margin (NIM). The research sample was carefully selected through purposive sampling and included six conventional banks listed on the Indonesia Stock Exchange from 2015 to 2022. The research uses a panel data regression fixed effect model as the analysis model. The results indicate that Loan Deposit Ratio (LDR), Operational Expenses to Operating Income (BOPO), and Net Performing Loans (NPL) have a significant impact on the profitability of conventional banking. In contrast, the research found no significant impact of the Current Ratio (CR) and Net Interest Margin (NIM) on the profitability of conventional banking. This research provides a comprehensive understanding of the complex relationship between crucial financial indicators and the profitability of conventional banking. The findings of this study could serve as a valuable reference for practitioners and decision-makers in the banking industry to develop optimal strategies to enhance financial performance.